Bioavailability of phosphorus from composts and struvite in acid soils - Carmo Horta (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective of this study was to assess the type and fractions of phosphorus (P) forms in composts and struvite and how these P forms affect the bioavailability of P in the soil. P fertilization was performed with compost from sewage sludge (CSS), compost from poultry litter (CPL) and struvite (SV) and compared with single superphosphate (SSP). P forms were quantified through a sequential fractionation scheme. The first extraction was performed with H2O, the second with 0.5 M NaHCO3, the third with 0.1 M NaOH and the fourth with 1 M HCl. The release of P over time, after soil P fertilization, was assessed by incubating the fertilizers with a low-P acid soil. P bioavailability was assessed through a micro-pot experiment with the incubated soils in a growth chamber using rye plants (Secale cereale L.). Inorganic P forms in the first two fractions represented ~50% (composts), 32% (SV) and 86% (SSP) of the total P; and in the HCl fraction, ~40% (composts), 26% (SV) and 13% (SSP) of the total P. Despite the variability of the P form fractions in the composts and struvite, the P release and bioavailability were similar among the fertilized treatments. The acidic nature of the soil, which improve solubility of Ca-P forms, and the high efficiency of rye, which favors P uptake, were factors that contributed to these results.